Crown development of Scots pine trees following thinning and nitrogen fertilization - Valinger, Erik (1993)
The effects of thinning and nitrogen fertilization, singly and in combination, on the growth of 45-year-old Scots pine (Pinus sylvestris L.) trees in northern Sweden, were studied from 1983-1988 inclusive. Sixteen trees were examined each year for crown development. The number of branches, shoot axes and buds produced, branch elongation on main axes, and dry weight production of shoot axes, needles, buds, cones, and dead material on live branches, were determined destructively on four trees per treatment. Both thinning and fertilization influenced the number of crown components produced annually. Branch elongation was increased by fertilization, and decreased by thinning. The weights of the components studied were increased more by fertilization than by thinning. Thinning promoted the distribution of growth to the lower crown, while fertilization promoted growth in the upper crown. Combined thinning and fertilization increased the weight of shoot axes, needles and buds more rapidly than did thinning or fertilization applied individually.